Konsep Kepemimpinan Strategis dalam Pendidikan: Mewujudkan Etika dan Pembelajaran Berkelanjutan - Salma Salsabila; Ajeng Fitria Khairunnisa; Tiffany Riskilla Hamde; Hesti Kusumaningrum (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to examine the role of strategic leadership in realizing ethics and sustainable learning in educational settings. Through study literature analysis, this research investigates theories and findings related to strategic leadership in education and its integration with ethical principles. The findings of this study show that successful strategic leadership not only prioritizes the achievement of organizational goals, but also affirms ethical principles as the basis for decision-making and management of educational institutions. Leaders who uphold ethics can build a school environment that is fair, inclusive and transparent, and ensure the fulfillment of the rights of all parties involved. In addition, educational leaders must have a vision that encourages innovation in the learning process by strengthening the role of teachers, utilizing technology and updating the curriculum that is appropriate and relevant to today's challenges. Continuous learning focuses not only on academic achievement, but also on developing students' character, skills for the 21st century and social responsibility. In addition, far-sighted strategic leadership plays a crucial role in driving innovation in learning and the application of technology to meet global challenges and build a sustainable education system. This research contributes ideas for the development of a responsive, ethical and sustainability-focused educational leadership model.